Guide on surveying the economic contribution of the copyright-based industries (WIPO GenevaCH, 2003)
Provides practical guidance to all countries wishing to survey and measure the size of their creative and information sector. Surveys the economic contribution of the copyright-based industries and provides quantifiable characteristics of this contribution.
Keywords: COPYRIGHT